Fluorescent Bead–DNA Conjugate‐based Dual Signal Amplification Technology. (21st April 2016) - Sonawane, Mukesh Digambar; Lee, Hae Ryong; Nimse, Satish Balasaheb; Song, Keum‐Soo; Kim, Taisun; Kim, Sang Cheol
Abstract : It is the first report of the development of a dual signal amplification technology for DNA microarrays by synthesizing and applying the FB–DNA conjugates. Abstract : One of the major challenges in DNA microarrays for their widespread application is assay sensitivity. Therefore, to achieve higher sensitivity, we developed a dual signal amplification technology based on the fluorescence beads (FB). It is the first report of the development of a dual signal amplification technology for DNA microarrays by synthesizing and applying the FB–DNA conjugates. The FB–DNA conjugates and Cy5‐T1‐FB‐mixed‐DNA demonstrated ~250–325‐fold increase in sensitivity when compared with the conventional use of Cy5‐labeled oligonucleotides such as Cy5‐T1. Furthermore, the Cy5‐T1‐FB‐mixed‐DNA demonstrated ~5–1.3‐fold increase in the sensitivity when compared with that of the FB–DNA conjugates alone.